Stochastic Analysis of Markov Chain In Finite State: Empirical Evidence on Nigerian Current Account Net Movements - UCHENNA, Amadi Innocent; UCHECHI, Ahana; ELE, Chims Benjamin (Journal of Entrepreneurial and Business Diversity, 2023)
Purpose: The Current Account is an essential indicator of an economy's speed. It is because it is defined as the sum of trade balance, net income from abroad, and net current transfers. Therefore, the impression of the Markov chain is a viable instrument for investigating the Nigerian Current Account (NCA) formation in finite since each finite state interconnects for suitable decision-making. Thus, this dissertation studied the stochastic analysis of the Markov chain on NCA data (2004-2022).Methodology:The NCA data were transformed into a 3-step transition probability matrix solution to cover independent years. The future NCA data changes were known by introducing a time interval of three years as row vectors.Findings: The solution matrix of the stochastic analysis showed that 2004-2012 has the highest probability of reducing payments by 72%, the year 2005-2013 has the highest probability of reducing by 66%, and finally, 2014-2022 has the highest probability of no-change in payments of goods and services by 3.3%.Implication:Finally, other statistical variations were also considered and discussed in this paper. All this informs the Nigerian economy on the proper way to make vital decisions effectively and are hopeful for future investment plans both short and long term respectively.